1992
DOI: 10.1007/bf00222860
|View full text |Cite
|
Sign up to set email alerts
|

The location of major genes and associated quantitative trait loci on chromosome arm 5BL of wheat

Abstract: Chromosome 5B of bread wheat is known to carry two major genes giving rise to genetic disorders, Ne1 for hybrid necrosis and Vg for winter variegation. Additionally, in many european winter wheat varieties this chromosome is represented in a translocated form, with 5BL-7BL, 5BL-7BS chromosomes rather than the normal 5B and 7B forms of the standard variety Chinese Spring. Genetic analysis has been carried out to map these genes and the translocation break point, and to investigate their pleiotropic effects or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In the Fi monosomic hybrid resulting from this cross, the 5BS-7BS chromosome is lacking and a trivalent is formed at meiosis with the configuration 5BS-5BL/5BL-7BL/7BL-7BS in which the 5BS and 7BS arms from the donor variety are left unpaired and therefore cannot undergo recombination. Because the translocation is large and involves a breakpoint at or very close to the centromere (Miura et al 1992), this trivalent is usually found in about 98% of metaphase cells, and normally disjoins with the 5BS-5BL and 7BL-7BS chromosomes going to one of the daughter cells and the 5BL-7BL chromosome to the other. In the backcross generations, the same chromosomal configuration is maintained until the final selfing when, because disomics are extracted, the gametes contributing to the zygote must each have the normal 5BS-5BL and 7BS-7BL chromosomes.…”
Section: Derivation Of Aneuploid and Substitution Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Fi monosomic hybrid resulting from this cross, the 5BS-7BS chromosome is lacking and a trivalent is formed at meiosis with the configuration 5BS-5BL/5BL-7BL/7BL-7BS in which the 5BS and 7BS arms from the donor variety are left unpaired and therefore cannot undergo recombination. Because the translocation is large and involves a breakpoint at or very close to the centromere (Miura et al 1992), this trivalent is usually found in about 98% of metaphase cells, and normally disjoins with the 5BS-5BL and 7BL-7BS chromosomes going to one of the daughter cells and the 5BL-7BL chromosome to the other. In the backcross generations, the same chromosomal configuration is maintained until the final selfing when, because disomics are extracted, the gametes contributing to the zygote must each have the normal 5BS-5BL and 7BS-7BL chromosomes.…”
Section: Derivation Of Aneuploid and Substitution Linesmentioning
confidence: 99%
“…The translocation is an old one and can be traced to the variety 'Noe', which appeared in France in the latter part of the 19th century and probably has Russian origins (Lupton 1987). Miura et al (1992) found that the translocation was transmitted preferentially from plants in which it was heterozygous. They also found some evidence for a yield advantage associated with the 5BL arm.…”
mentioning
confidence: 99%
“…Some major QTLs for important yield-related traits other than SLl have been reported. For example, QTLs have been identified on chromosome 5B that affect spikelet number per spike and Gns (Miura et al, 1992 ), and Börner et al ( 2002 ) detected major QTLs on chromosomes 2DS, 4AL, and 5AL for Gns and grain weight per spike by studying a BC 2 F 1 population. In addition, eight QTLs on chromosomes 1D, 2A, 3D, 6A, 7A, and 7D for Gns have been found (Huang et al, 2004 ), and Li et al ( 2007 ) identified five QTLs for Ssn on chromosomes 1A, 4A, 6B, 7A, and 7D and five QTLs for Fsn on chromosomes 2A, 5D, 6B, and 7D using an RIL population.…”
Section: Introductionmentioning
confidence: 99%
“…Law (1965Law ( , 1966 proposed to employ chromosome substitution lines or recombinant inbred chromosome lines to determine the genetic factors that aVect quantitative traits. Using such a strategy coupled with genetic markers, loci for yield-related traits of wheat have been assigned to chromosomes 3A (Shah et al 1999;Campbell et al 2003), 4A (Araki et al 1999), 5A (Snape et al 1985;Kato et al 2000), 5B (Miura et al 1992), and 7B (Law 1967). Berke et al (1992) explored quantitative trait loci (QTL) aVecting seven agronomical traits using a complete set of reciprocal chromosome substitutions between wheat cultivars 'Wichita' and 'Cheyenne'.…”
Section: Introductionmentioning
confidence: 99%